(3eSfO GdEeGe CMeO Hf MfHds - (3GdTjHGfj, GdeQhRj, GdHZOGOj, CHh YHO Gddg, CMeO Hf eMeO Hf MfHd, J (B241(3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdJUdjI eSfO GdCfUGQ , QVj Gddg JYGdi Yfge MOjK CHj GdefPQ CHj Hf cYH eeG QhGg Yfg YeQ Hf GdNWGH QVj Gddg JYGdi YfgeG , Yf QShd Gddg Udi Gddg Ydjg hSde (B- (3MOKfG YHO Gddg MOKfj CHj KfG jYbhH Hf EHQGgje Hf SYO , Yf CHjg , Yf eMeO Hf ESMGb , ajef TgO HOQGs
(3BNQgG (B:s
(3MOjK eWQ Hf YcGeS Yf CHj ESMGb , Yf eWQ Hf YcGeS , bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3EPG bVi Gddg ejJI YHO HCQV ,Yd dg EdjgG MGLI MOKfG YHO Gddg , MOKfG eMeO HfYaQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 203s
(3eYLe GdeDdajf (B1 / 261s
(3cTa GdXfhf (B2 / 1680s
(3JGQjN GdESdGe (B/ (3hajGJ (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs